EFFECT OF GAMMA IRRADIATION OF SEEDS ON GROWTH, SEX EXPRESSION AND YIELD IN BOTTLE GOURD (LAGENARIA SICERARIA STANDL.) - LAL, ANIL KUMAR; CHATURVEDI, O.P.; LAL, S. K.; KUMAR, P.R. (Annals of Agricultural Research, 2014)
In the present study, bottle gourd seeds of variety Pusa Summer Prolific Long were treated with gamma rays at different doses of 0.5, 0.75, 1.0, 1.25, 1.5, 1.75, and 2.0 k Rad. It was observed that I k Rad of gamma radiation is the most effective dose for inducing better growth, sex expression and yield of fruit in bottle gourd. However, the gamma radiation doses were found to have harmful effect on the germination. The germination percentage decreased with increasing doses of gamma irradiation.